Security Threats to Wireless Networks and Modern Methods of Information Security - Seleman, Yasser A (Arab Journal for Sciences and Research Publishing, 2016)
Network is a technology used to connect computers and devices together. They allow people the ability to move easily and stay in touch while roaming the Internet in the coverage area. This increases efficiency by allowing data entry and access to the site. Comparing wireless networks wired networks in terms of cost, we find that wired networks are more expensive due to the cost of the network connections of electricity and running and add computers and change their positions to suit the network supply. As a result, the use of widespread wireless networks. But there are security gaps in these networks may cause problems for users Security holes intended problem or weakness in the wireless network system may make it easier for hackers to penetrate and steal sensitive data and causing material losses to individuals and companies. Knowing security holes and contributes significantly to the wireless network is immune from attempts to infiltrate and penetration design